2016
DOI: 10.1016/j.vaccine.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 adjuvant in combination with virus-like particles elicit a humoral response against HIV

Abstract: Human Immunodeficiency Virus (HIV) Virus-Like Particles (VLPs) composed of HIV Gag and HIV gp120/gp41 envelope are a pseudovirion vaccine capable of presenting antigens in their native conformations. To enhance the immunogenicity of the HIV Env antigen, VLPs were coupled to VesiVax Conjugatable Adjuvant Lipid Vesicles (CALV) containing one of four toll-like-receptor (TLR) ligands, each activating a receptor with distinct cellular localization and downstream pathways. C57BL/6 mice were vaccinated by intranasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Yet, the nature of TFH-favoring innate immune stimuli has remained largely unknown. Several studies have addressed the impact of TLR activation on the development of TFH cells and germinal center formation in mice 63,64,65,66,67,68,69 . For instance, it has been reported that monocyte-derived dendritic cells (Mo-DC) are important stimulators of TFH cell responses in mice, especially when activated via TLR9 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the nature of TFH-favoring innate immune stimuli has remained largely unknown. Several studies have addressed the impact of TLR activation on the development of TFH cells and germinal center formation in mice 63,64,65,66,67,68,69 . For instance, it has been reported that monocyte-derived dendritic cells (Mo-DC) are important stimulators of TFH cell responses in mice, especially when activated via TLR9 70 .…”
Section: Discussionmentioning
confidence: 99%
“…In the vaccination experiments, we observed that ncRNA VLPs induced longer-lasting humoral responses. We believe ncRNA VLPs are able to more efficiently activate follicular helper T cells, leading to better memory induction, as has already been shown with a TLR3 ligand encapsidated in HIV-derived VLPs (53). This question is under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 70%
“…Resiquimod, a TLR7/8 agonist also known as R848, has been shown to restrict HIV1 infection of monocytes in a post-entry/pre-reverse transcription SAMHD1independent manner [97]. Together with other molecules, this TLR agonist might serve as adjunct for vaccine strategies in order to elicit antiviral immune defenses against HIV [98,99]. Also, the efficacy of MGN1703/lefitolimod to activate NK cells and reverse HIV latency is being investigated in a phase 1/2 study in HIV1 ART-treated patients (Table 2).…”
Section: Tlr Agonists To Optimize the Induction Of Ifnmentioning
confidence: 99%